THE CHARACTERISTICS OF FORMING THE VOLUNTARY ASPECTS OF STUDENTS IN PROFESSIONAL DIRECTION IN THE EDUCATION AND EDUCATION IN THE SCHOOL - Saliyeva Dilorom Abdullayevna (Galaxy International Interdisciplinary Research Journal, 2023)
The article explains the importance of the volitional process from their individual characteristics and the importance of the formation of risk characteristics when directing students to the profession.